Analisis Efisiensi dan Produktivitas Sektor Industri Mikro dan Kecil di Provinsi Lampung - Gilang Wicaksono; Emi Maimunah (Moneter : Jurnal Ekonomi dan Keuangan, 2026)
This research addresses a paradoxical phenomenon in Lampung Province's Micro and Small Industry (MSI) sector (2018-2022), where high technology adoption is accompanied by declining business units and income inequality. The objective is to evaluate technical efficiency and productivity changes across 15 regencies/cities using the Variable Returns to Scale (VRS) Data Envelopment Analysis (DEA) model and the Malmquist Productivity Index (MPI). Results show an average technical efficiency of 0.838, indicating a 16.2% room for output improvement. Mesuji Regency serves as the benchmark with perfect efficiency. The main inefficiency stems from labor slack (averaging 3,458 people per region), reflecting disguised unemployment. The Malmquist index records an asymmetric productivity growth of 2.1% annually, entirely driven by technological progress (3.5%), while internal managerial efficiency contracted (-1.4%). Consequently, technology adoption requires structural intervention; regional governments must prioritize vocational training and basic managerial strengthening to reduce labor slack and break the MSI inefficiency cycle.